A Case of Effective Mepolizumab Induction Therapy for Severe Eosinophilic Granulomatosis with Polyangiitis Diagnosed by Eosinophilic Cholecystitis and Interstitial Nephritis - Hattori, Keita; Teramachi, Yuri; Kobayashi, Yoshinori; Ito, Takeshi; Morinaga, Takatoshi; Tamai, Hirohumi; Yamamoto, Yoshihiro (Case Reports in Rheumatology, 2021)
A 66-year-old man with a history of bronchial asthma and sinusitis was admitted with cholecystitis and peripheral neuropathy. The histopathological findings of the gallbladder revealed necrotic vasculitis and granulomatous inflammation with marked eosinophilic infiltration. Kidney biopsy also showed marked eosinophilic infiltration in the tubulointerstitial area and eosinophilic tubulitis. He was diagnosed with eosinophilic granulomatosis with polyangiitis (EGPA) and treated with corticosteroids. However, he showed no response. Therefore, he was administered mepolizumab 300 mg, which resulted in clinical improvement, including normalization of the eosinophil and CRP levels. We herein describe the first case of successful induction therapy of EGPA using mepolizumab.